Allergic diseases and risk of hematopoietic malignancies in a cohort of postmenopausal women: A report from the Iowa Women’s Health Study - Linabery, Amy M. (2014)
BACKGROUND: Allergic diseases signify immune dysregulation attributable to underlying genetics and environmental exposures. Associations between various allergies and hematopoietic cancers have been observed, albeit inconsistently, however few prospective studies have examined the risk, and even fewer among older adults. METHODS: We examined risk of incident hematopoietic cancers in those reporting allergic diseases in a population-based cohort of 22,601 older women (Iowa Women’s Health Study). Self-reported allergic status, including asthma, hay fever, eczema and/or other allergies, was determined via questionnaire in 1997 (mean age=72 years, range 63–81 years). Incident cancers were ascertained by linkage with the Iowa Cancer Registry from 1997–2011. Cox proportional hazards regression was performed to estimate multivariate-adjusted hazard ratios (HR) and 95% confidence intervals (CIs) for myeloid (N=177) and lymphoid (N=437) malignancies, respectively. RESULTS: Allergic diseases were not associated with risk of myeloid (HR=1.00, 95% CI: 0.72–1.37) or lymphoid (HR=0.99, 95% CI: 0.81–1.22) malignancies overall, or for most allergic and malignant subtypes examined. Self-reported asthma was positively associated with development of myelodysplastic syndrome (MDS, HR=2.00, 95% CI: 0.93–4.32). In addition, there was a 30–40% decrease in risk of both lymphoid and myeloid cancers in those reporting rural residences but no association in those reporting urban residences; the interaction between residence and allergy was statistically significant for lymphoid malignancies (P(interaction)=0.05). CONCLUSIONS AND IMPACT: These results suggest asthma may contribute to the pathogenesis of MDS, a finding consistent with the chronic antigen stimulation hypothesis. Susceptibility differences by location of residence are concordant with the hygiene hypothesis and merit additional exploration.